Revision of the Mediterranean and southern African Triglochin bulbosa complex (Juncaginaceae) - Mucina, Ladislav; Köcke, A.; von Mering, S.; Kadereit, J. (2010)
The Triglochin bulbosa complex (Juncaginaceae) from the Mediterranean region and Africa is revised. One new species, Triglochin buchenaui Kocke, Mering & Kadereit, and two new subspecies, Triglochin bulbosa subsp. calcicola Mering, Kocke & Kadereit and Triglochin bulbosa subsp. quarcicola Mering, Kocke & Kadereit, are described from South Africa. The only two Mediterranean taxa in the complex (Triglochin barrelieri, T. laxiflora) are elevated to species rank. Altogether seven species and four subspecies are recognised: Triglochin barrelieri, T. buchenaui, T. bulbosa subsp. bulbosa, T. bulbosa subsp. calcicola, T. bulbosa subsp. quarcicola, T. bulbosa subsp. tenuifolia, T. compacta, T. elongata, T. laxiflora and T. milnei. An identification key, detailed descriptions and accounts of the ecology and distribution of the taxa are provided. An IUCN conservation status is proposed for each taxon.